Toad Venom: A Key Component in the Drug Development with Promising Prospects - NIMITHA, CHEROOR R.; RASHEED, VAZHANTHODI ABDUL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Toad venom, a complex mixture of bioactive molecules, has been utilized for centuries in traditional medicine due to its diverse pharmacological properties, including antimicrobial, antipyretic, and anticancer activities. Comprising biogenic amines, bufadienolides, steroids, and peptides, this natural secretion has shown promise in treating various disorders by ancient people. Recent studies substantiate its potential as a complementary therapeutic agent in combination with existing ones in the future, particularly in combating multidrug-resistant microbes. This review highlights the medicinal properties of specific toad venom components, demonstrating efficacy against congestive heart failure, atrial fibrillation, breast carcinoma, and improved circulation. Further research is warranted to harness the full potential of toad venom-derived compounds, offering prospects for developing novel, multifunctional drugs that surpass existing treatments.